BİYOMETRİK GÖRÜNTÜLERDE KİMLİK DENETİMİ İÇİN ŞİFRELEME TEKNİKLERİ KULLANILARAK DAMGALAMA - USER, MUHAMMET ALİ (Fırat Üniveristesi, 2022)
Today, passwords are used first, respectively, to enter buildings or systems. Biometric data is used to increase the level of security after passwords are stolen or obtained. For higher security, it is aimed to provide high security by using smart card, biometric data and password. In the parts where this high security is required, the password, which is the weakest point of the authentication, must be protected. For this purpose, in the study, the password to be entered into the system for the authentication of biometric data was made into a text file by RSA encryption and hidden in the cover image with steganography, and the stamp image was obtained and the stamp was placed in the biometric data with DWT stamping. By investigating biometric data, encryption types and stamping types; Information about image quality measurement PSNR and MSE is given. In encryption, the mathematical explanation and application of RSA encryption has been made. In stamping, the necessary protection of ownership is provided by using DWT. The MATLAB program was used in encryption, steganography and stamping and the results were given.

Today, passwords are used first, respectively, to enter buildings or systems. Biometric data is used to increase the level of security after passwords are stolen or obtained. For higher security, it is aimed to provide high security by using smart card, biometric data and password. In the parts where this high security is required, the password, which is the weakest point of the authentication, must be protected. For this purpose, in the study, the password to be entered into the system for the authentication of biometric data was made into a text file by RSA encryption and hidden in the cover image with steganography, and the stamp image was obtained and the stamp was placed in the biometric data with DWT stamping. By investigating biometric data, encryption types and stamping types; Information about image quality measurement PSNR and MSE is given. In encryption, the mathematical explanation and application of RSA encryption has been made. In stamping, the necessary protection of ownership is provided by using DWT. The MATLAB program was used in encryption, steganography and stamping and the results were given.
Watermarking by using encryption techniques for authentication in biometric images
Keywords: Mühendislik Bilimleri